Path Analysis of Healthy Cognitive Life Skills Effect on Children’s Self-Esteem, Knowledge, Critical Thinking, and Decision-Making Skills - Ratih Indraswari; Bagoes Widjanarko; Riza Hayati Ifroh (Jurnal Keperawatan Soedirman, 2026)
Early engagement in risky sexual behavior among Indonesian adolescents is often associated with limited reproductive health knowledge and environmental factors. This study evaluated the effectiveness of a Healthy Cognitive Life Skills (HCLS) educational model using interactive games to improve children's reproductive health knowledge, self-esteem, critical thinking skills, decision-making skills, and attitude toward reproductive health. A quasi-experimental study with a non-equivalent control group pretest-posttest design was conducted among 254 children aged 9-10 years from two elementary schools in Semarang City, Indonesia. Data were collected using validated questionnaires and analyzed using partial least squares structural equation modeling (PLS-SEM). The HCLS educational model did not demonstrate a significant direct effect on cognitive life skills. However, it significantly improved self-esteem, which subsequently mediated improvements in reproductive health knowledge, critical thinking skills, and decision-making skills. The intervention did not directly improve attitudes toward reproductive health, although cognitive life skills and self-esteem were positively associated with attitudes. These findings suggest that game-based HCLS education primarily enhances children’s cognitive skills through strengthening self-esteem rather than through direct educational effects. Incorporating strategies that specifically target the affective domain may further improve attitudes toward reproductive health.